Assessing the Effectiveness of Add-On Therapy of Palmitoylethanolamide to Standard Therapy in Diabetic Peripheral Neuropathy - Velusamy Sivakumar; Thangavelu Saravanan; V.K. Damini (Journal of Pharmaceutical Care)
Background: Diabetic Peripheral Neuropathy (DPN) is a common yet challenging complication of diabetes, particularly in managing neuropathic pain. Palmitoylethanolamide (PEA), a naturally occurring nutraceutical from the ALIAmides group, has demonstrated potential for pain modulation, inflammation reduction, and improving quality of life.